I grandi eventi: un osservatorio privilegiato sulla ricon?gurazione degli spazi. Il caso di Zaragoza 2008 (Altre Modernità, 2012)
The paper Mega-events: a privileged observatory on the reconfiguration of spaces, landscapes and identities in the contemporary city. The case of Zaragoza 2008 proposes an analysis of urban restoration processes in contemporary European cities, through the case study of Zaragoza. Zaragoza represents a useful case study in order to point out how contemporary cities face the economic and social transition, from the traditional industrial model to the contemporary response to global urban challenges. The case of Zaragoza synthesizes the main strategies adopted by local administrations in reshaping cities, adopting urban renewal programs and policies. The transformation of Zaragoza started at the end of the eighties with the approval of the new Masterplan (Plan General de Ordenación Urbana). After that, in 1998, a commission composed by local administrators and stakeholders, adopted a Strategic plan, which promoted the regeneration and the local development of the city until 2015. In 2004 Zaragoza obtained the nomination as host city for the International Expo of 2008. The challenge of the Expo gave a new impulse to all the programmed projects, spread in all the neighborhoods, which converged towards the scheduled event of 2008.The core of the research presented in this paper concerns the analysis of the policies, the strategies and practices promoted by the city of Zaragoza for the Expo 2008 and their consequences in reshaping and reorganizing the city after the conclusion of the event.